STRATEGI BRANDING DINAS KEBUDAYAAN DAN PARIWISATA KOTA MALANG DALAM MEMBENTUK IMAGE SEBAGAI KOTA PARIWISATA - Albet, Pransiskus; Indra Dewi, Sulih (Unitri Press, 2019)
This study aimed to find out how the branding strategy of the Culture and Tourism Agency (Disbudpar) of Malang in shaping the image of Malang as a tourism city and to know what obstacles affect the application of the branding strategy. This study used a qualitative research by analyzing the branding strategy of Disbudpar Malang. The data collection techniques carried out in field research and to obtain information and data was through interviews and documentation. The results of this study indicated that the branding strategy of Disbudpar Malang in shaping the image of Malang were as follow, first brand positioning for example by the formation of the beautiful Malang city branding, second brand identity by making the tag line and logo of beautiful Malang, third brand personality for example Malang is known as a cool city, fourth brand communication by promotion on social media events and relationships with stakeholders. The fifth startegy was brand equity for example by making beautiful destinations such as thematic villages and beautiful city parks. The constraints from the brand strategy were first, from the publication of beautiful Malang in print media was considered less reflecting the image of Malang and the presence of those who criticized the beautiful Malang logo, second there were some villages that were still less of awareness in tourism, third in terms of destinations there were lack in facilities and infrastructure, fourth the limited funds to conduct the activities or events.